Variation on agro-morphological traits in Nepalese foxtail millet (Setaria italica (L) P Beauv) - Amgai, RB; Pantha, S; Chhetri, TB; Budhathoki, SK; Khatiwada, SP; Mudwari, A (Agronomy Journal of Nepal, 2013)
Foxtail millet (Setaria italica (L) P Beauv) falls on the category of underutilized crops in Nepal and mainly cultivated in Karnali region of the country. It is hardy crop and considered as one of the potential crops for future food security with respect to climate change. Five accessions of Nepalese foxtail millet were purposefully selected for evaluation of the agro-morphological characteristics. Foxtail landraces from Dolpa, Mugu, Bajura, Bajhang and Lamjung districts of Nepal were evaluated at Khumaltar, Lalitpur, Nepal during 2010. The plot size was 1m2 and there were five samples. Days to heading and days to maturity varied from 33-56 and 59 to 87 days after germination respectively. Similarly, flag leaf length/breadth ratio, flag leaf sheath length, ligule length, peduncle length, peduncle exertion and plant height varied from 3.84-10.90, 5.47-9.84 cm, 0.1-0.2 mm, 10-22.57 cm, 2.7-13.58 cm and 41.67-120 cm, respectively. Fruit and apiculus color varied from straw to black. All accessions were actively growing with very slight lodging. Similarly, the thousand grain weight varies from 1.064 g to 2.172 g. This variation is useful in foxtail millet breeding program. Similarly, the significant correlation between thousand kernel weight and total basal tiller (r=-0.975) showed that foxtail millet lines with low tillering ability is better for yield enhancement. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7528 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.133-138